Enhancing Financial Management Practices of Small and Medium Enterprises (SMEs) through the SI-APIK Application: A Community Service Approach in Jakarta - Sofyan, Mohammad; Kumala, Ratih (Bisma : Bimbingan Swadaya Masyarakat, 2024)
This community service program aimed at enhancing the financial management practices of Small and Medium Enterprises (SMEs) in Jakarta through the SI-APIK application. The program addressed the challenges SMEs face in managing their finances by providing targeted training and hands-on use of the SI-APIK application, designed to help businesses maintain accurate financial records in accordance with SAK-EMKM standards. The intervention resulted in a significant improvement in financial literacy, with 75% of participants gaining a clear understanding of financial reporting standards. Furthermore, 90% of the SMEs adopted the SI-APIK application for regular financial transaction recording, and 60% of participants reported improved access to financing due to more transparent financial documentation. The study demonstrated that digital financial tools, when combined with financial literacy training, can significantly enhance the financial management capabilities of SMEs, contributing to better decision-making, business growth, and financial sustainability. The study also identified areas for improvement, including the need for ongoing digital literacy training and follow-up support to ensure long-term adoption of digital tools.